The influence of green quality of work life, green employee engagement, and green rewards on green employee retention in SME employees - Putri Wicaksari; Asep Rokhyadi Permana Saputra; Aminah Nur Rahmah (Small Business International Review)
One of the biggest challenges for employers is retaining employees, who are crucial for enhancing company performance, especially in SMEs. This research aims to determine the influence of Green Quality of Work Life, Green Employee Engagement, and Green Rewards on Green Employee Retention. The study employs a quantitative approach, sampling 204 SME employees in Indonesia, determined using the Slovin formula with a 7% margin of error. Quota sampling techniques and questionnaires distributed via Google Forms were used for data collection. The analytical tool used is SEM PLS version 4, incorporating validity and reliability testing, Fornell-Larcker Criterion, Heterotrait-Monotrait Ratio, and hypothesis testing, with responses measured on a 5-point Likert scale. The results indicate that Green Quality of Work Life does not significantly affect Green Employee Retention. However, Green Employee Engagement and Green Rewards have a significant impact on Green Employee Retention. The theoretical contribution of this research lies in the application of financial motivation theory, particularly regarding the lowest mean of the first indicator. This theory could be valuable as a moderator in future research models. Practically, the study suggests that increasing salaries and providing knowledge and training as forms of additional expertise can enhance employee retention.